Pro Android Graphics - Jackson, Wallace (Apress : Imprint: Apress, 2013)
Pro Android Graphics is a comprehensive goldmine of knowledge and techniques that will help you design, create, and optimize 2D graphics for use in your Android Jelly Bean applications. Android application developer and expert multimedia producer Wallace Jackson of Mind Taffy Design shows you how to leverage Android's powerful graphics APIs in conjunction with professional open source graphics design tools such as GIMP 2.8.6 and more. You'll learn about: The foundational graphics concepts behind the three core new media areas (digital imaging, digital video, and 2D animation) which relate to graphics design, and how to optimize these new media assets for your Android applications across iTVs, tablets, eReaders, game consoles, and smartphones. Digital imaging techniques for Android apps design, including graphics design layouts and graphical user interface elements, and how to use image compositing techniques to take your digital imaging to far higher levels. Advanced image compositing and blending techniques, using Android's PorterDuff, NinePatch, and LayerDrawable classes. Advanced 2D animation techniques, using Android's Animation and AnimationDrawable classes. Digital video optimization, playback, and streaming, using open source 3D (Terragen 3) and video (VirtualDub) applications, as well as professional video editing applications such as Squeeze Pro 9. You'll use these software packages with Android's VideoView and MediaPlayer classes, and add compositing to enhance your end-users' digital video experience.